Implementation of Competency and Conservation Based Curriculum to Improve Graduates’ Quality to be Competence and Conservation-Minded - Asrori, Asrori (Dinamika Pendidikan, 2016)
This research aims to analyze the implementation of Competency and Conservation Based Curriculum in order to improve the quality of graduates of Economics Faculty of Universitas Negeri Semarang (UNNES). The goal of this study was to provide information, policy,  and recommendations to improve the quality of graduates based on lectures behavior. The respondents of this research were lecturers of Faculty of Economics. Research data were collected by using questionnaires. Descriptive statistics and inferential statistical multiple linear regression were employed to analyze data. This study provided empirical support that lecturers’ ability and commitment positively contributed to the implementation of Competency and Conservation Based Curriculum to improve the quality of graduates to be competence and conservation-minded. This study also proved that while lecturers’ ability and commitment play an important role, their commitments do not affect the implementation of Competency and Conservation Based Curriculum. Based on the results of this study, it is recommended that lecturers’ ability to implement the Competency and Conservation Based Curriculum needs to be improved. Workshops and training should be given to lecturers in order to help them to create learning apparatus such as syllabus, lesson plans and teaching materials, as well as the evaluation of Competency and Conservation Based Curriculum.